2020
DOI: 10.1002/ajh.26068
|View full text |Cite
|
Sign up to set email alerts
|

First‐line treatment of double‐hit and triple‐hit lymphomas: Survival and tolerance data from a retrospective multicenter French study

Abstract: Historically, double or triple hit lymphoma (DHL and THL) have poor outcomes with conventional chemotherapy, but there is currently no guideline. We report the French experience in managing DHL and THL in first line using collective data on both survival and tolerance. All consecutive patients with newly diagnosis of large B‐cell lymphoma with MYC, BCL2, and/or BCL6 rearrangements, as determined by FISH between January 2013 and April 2019 were included. Based on the eligibility criteria, 160 patients were sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 24 publications
2
34
0
Order By: Relevance
“…Similar results were obtained by independent studies in 2014( n = 129),2017(two studies, n 1 = 159, n 2 = 117) and 2021( n = 160). Auto-SCT after a front line or intensive chemotherapy in DHL patients did not affect 3-year PFS or OS after first CR [ 13 , 33 , 36 , 39 ]. On the other hand, these studies again emphasize the importance of intensive therapy compared to front-line therapy in improving the 3-year RFS [ 36 ].…”
Section: Diagnosis Prognosis and Current Treatmentmentioning
confidence: 99%
“…Similar results were obtained by independent studies in 2014( n = 129),2017(two studies, n 1 = 159, n 2 = 117) and 2021( n = 160). Auto-SCT after a front line or intensive chemotherapy in DHL patients did not affect 3-year PFS or OS after first CR [ 13 , 33 , 36 , 39 ]. On the other hand, these studies again emphasize the importance of intensive therapy compared to front-line therapy in improving the 3-year RFS [ 36 ].…”
Section: Diagnosis Prognosis and Current Treatmentmentioning
confidence: 99%
“…Interestingly, the CR rates between the two groups were not substantially different. A previous study revealed that DH DLBCL might bene t more from intensi ed chemotherapy [30]. Therefore, we examined the disease course of each DH DLBCL in our study cohort.…”
Section: Clinical Data Of Dh (+) Dlbcl Patientsmentioning
confidence: 99%
“…Also, a large, recently published French ret ro spec tive study eval u ated 160 patients with HGBL (with MYC and BCL2 and/or BCL6) and dem on strated a sig nifi cantly lon ger PFS for inten sive ther apy vs R-CHOP. 18 HGBL-NOS cases are much rarer, and hence, there are a pau city of data to inform on opti mal treat ment.…”
Section: Approach To Hgbl With Myc and Bcl2 And/or Bcl6 Rearrangementsmentioning
confidence: 99%